Design, synthesis, and biological evaluation of 2,4-dimorpholinopyrimidine-5-carbonitrile derivatives as orally bioavailable PI3K inhibitors - Huang, Daowei; Yang, Jixia; Zhang, Qingwei; Zhou, Xiaolei; Wang, Yanbo; Shang, Zhenhua; Li, Jianqi; Zhang, Baoyin (Frontiers in Pharmacology, 2024)
Phosphoinositide-3-kinase (PI3K) is overexpressed in many tumors and is, thus, an ideal target for cancer treatments. Accordingly, there is an urgent need for the development of PI3K inhibitors with high potency and low toxicity. In this study, we designed and synthesized a series of 2,4dimorpholinopyrimidine-5-carbonitrile derivatives, which were evaluated for their PI3K inhibitory potency. Compound 17p demonstrated comparable PI3Kα inhibitory activity (IC50: 31.8 ± 4.1 nM) to the positive control, BKM-120 (IC50: 44.6 ± 3.6 nM). In addition, 17p showed significant inhibitory activity against PI3Kδ (IC50: 15.4 ± 1.9 nM) and significant isoform selectivity against PI3Kβ, PI3Kγ, and mTOR. Furthermore, 17p exhibited good antiproliferative activities against cancer cell activity and good safety in the Ames and hERG tests, while having outstanding liver microsomal stability in vitro, with half-lives of 38.5 min in rats and 127.9 min in humans. In addition, in an apoptosis assay, 17p could induce dose-dependent cytotoxicity in the ovarian cancer cell line A2780.In a pharmacokinetic study, 17p was stable (T½: 2.03 h) and showed high bioavailability (46.2%). Collectively, these results indicate that 17p could be a promising PI3K agent for cancer treatment.